Perpetual Peace: An Analysis of Kant’s Theory of Peace in Terms of The Islamic Worldview - Iqbal Maulana Alfiansyah; Mohamad Latief; Naqia Salsabila Taslim (Nalar: Jurnal Peradaban dan Pemikiran Islam, 2022)
This study critically discussed the concept of 'perpetual peace' according to Immanuel Kant. For Kant, peace is absolute, and war must be avoided. Kant's concept of peace departs from his philosophical ideas about humans and ethics. According to the researcher's hypothesis, Kant's concept of peace is problematic and not compatible with the concept of peace in Islam. This study aimed to describe Immanuel Kant's concept of perpetual peace and the concept of peace in Islam. In addition, it also analyzed how Kant's concept of perpetual peace is viewed from the Islamic worldview. This research was library research, and the methods used were descriptive, analytical, and comparative. This research concluded that Kant's concept of peace had several philosophical and practical problems. Philosophically, Kant's concept of peace revolves around the concept of man, ethics, and causality, which tend to deny the element of God in it. In practical terms, Kant's idea that war should not exist is a dream that is difficult to realize. His opinion about the peace triangle also leaves many problems. In contrast to that, in the view of Islam, war is allowed to fight injustice and aim for the creation of goodness or maslahah, justice, and global peace. War in Islam is also regulated based on ethical and humanitarian principles. This is based on the Islamic view of humans who simultaneously have a good and a wrong side. In addition, Islam focuses more on human nature and its perspective on reality and life to achieve peace. The Qur'an, with normative teachings such as equality between humans, justice, honesty, the nature of qanaah, can be used as a normative and practical basis for achieving perpetual peace